Notices of two Bills introduced into the last Parliament of Scotland, the one for the Registration of Births, Baptisms, Marriages, and Burials; the other for the establishment of a system of Free Trade (Proceedings of the Society of Antiquaries of Scotland, 1859)
The author discusses the various attempts to record births, deaths and marriages across the parishes of Scotland before a bill proposing a centralised registration of these events was put before the Parliament of Scotland and rejected. He also briefly touches on legislation that asserted the principle of Free Trade, but was similarly unsuccessful in Parliament.